2016
DOI: 10.18805/lr.v0iof.9487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drip fertigation on nutrient uptake and seed yield of pigeonpea [Cajanus cajan (L.) Millsp.] under westeren agroclimatic zones of tamil nadu

Abstract: Field experiments were conducted at Agricultural College and Research Institute, Coimbatore during August to February of 2011-12 and 2012-13 to study the effect of drip irrigation, fertigation levels and frequencies on seed yield and nutrient uptake of pigeonpea. Three fertilizer levels (75 %, 100 % and 125 % recommended dose fertilizer (RDF) through water soluble fertilizer and conventional fertilizers), three irrigation levels (50 % computed water requirement of crop (WRc), 75 % WRc and 100 % WRc) and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Overall, drip fertigation is a highly efficient method for fertilizer application, as it minimizes losses and mitigates adverse environmental effects on crop production. Both water and nutrients applied through irrigation will be efficiently used by the plants for photosynthesis, thereby causing greater synthesis, translocation and accumulation of carbohydrates [57]. Various studies have evaluated that fertigation is the only replacement of the conventional method that can achieve higher fertilizer use efficiency, reduce water and fertilizer application and lead to higher crop yield [58].…”
Section: Effect Of Split Supplication Of Npk Through Drip Fertigation...mentioning
confidence: 99%
“…Overall, drip fertigation is a highly efficient method for fertilizer application, as it minimizes losses and mitigates adverse environmental effects on crop production. Both water and nutrients applied through irrigation will be efficiently used by the plants for photosynthesis, thereby causing greater synthesis, translocation and accumulation of carbohydrates [57]. Various studies have evaluated that fertigation is the only replacement of the conventional method that can achieve higher fertilizer use efficiency, reduce water and fertilizer application and lead to higher crop yield [58].…”
Section: Effect Of Split Supplication Of Npk Through Drip Fertigation...mentioning
confidence: 99%
“…Overall, drip fertigation is a highly efficient method for fertilizer application, as it minimizes losses and the adverse environment effects on crop production. Both water and nutrients applied through irrigation will be efficiently used by the plants for photosynthesis, thereby causing greater synthesis, translocation, and accumulation of carbohydrates [18,52]. Various studies have evaluated that fertigation is the only replacement of the conventional method that can achieve higher fertilizer-use efficiency, reduce water and fertilizer application, and lead to higher economic returns [53][54][55][56][57][58][59][60].…”
Section: Effect Of Fertigation Levels On Cumin Plant Growth Yield-attributing Characteristics and Yieldmentioning
confidence: 99%
“…Several studies on drip fertigation at various parts of India on different vegetable crops have shown that the drip fertigation technique reduces fertilizer requirement by 40-60%, saves water by 20-60%, and increases the yield by 15-50% over the other methods of irrigation and fertigation [16,17]. The application of water and nutrient simultaneously to plants through fertigation enhances the photosynthesis process as plants produce new tissues to enhance biomass production [18]. Therefore, a field study was conducted to evaluate the potential of drip irrigation and fertigation on cumin yield, quality (oil content), and water-use efficiency grown under an arid zone of Rajasthan, India.…”
Section: Introductionmentioning
confidence: 99%
“…So along with water conservation some nitrogen amount can save by drip fertigation which will provide a supply of nitrogen uniformly and timely without polluting the environment by the leaching process. The drip fertigation decreases the requirement of fertilizer by 40-60% and enhances the crop yield by 15-50% over conventional method (Loganathan and Latha, 2016). The integrated application of irrigation water and nutrient (fertigation) to plants boosts the photosynthesis process so they produce new tissues to increase production of biomass.…”
Section: Introductionmentioning
confidence: 99%